PENGARUH HIDROTERAPI TERHADAP PENURUNAN KADAR GULA DARAH SEWAKTU PADA PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS BINJAI SERBANGAN KABUPATEN ASAHAN TAHUN 2020 - Tarigan, Herri Novita (Jurnal Penelitian Keperawatan Medik, 2021)
Hydrotherapy or water therapy is a method of treatment and healing with water for get the profit therapeutic in the treatment of disease. Diabetes Mellitus is a degenerative disease, which need an effort to suppress the increased.incidence of the disease. This,the aims of the research.to determine the effect of hydrotherapy to decrease blood sugar.random diabetes mellitus type 2 patients. The method of this research is a quasi experimental Two Grup pretest posttest design, the sampling, techniques used purposive sampling approach. Total respondent are 22 peoples, 11 respondents, for the control group and 11 intervention group. Data collection Uses A direct observation.sheet and measurement of blood sugar. Statistic analysis using independent T test. Indicates that there was a discreption between the average blood sugar and the action of hidroterapy in control grup and intervention groups (p=0,0001). Therefore it is assumed that hydrotherapy.would lower the blood sugar when DM 2, hydrotherapy patients can be used as a hyperglycemic management of diabetes mellitus.